A review of trip and parking generation rates in the Philippines. - Regidor, Jose Regin F.
The practice of transportation engineering and planning has employed trip and parking generation rates to determine the number of trips generated and attracted by developments, as well as the required number of parking spaces for facilities. Trip generation serves as an input to modeling transportation requirements and traffic flows influenced by the development. For example, a residential condominium may directly impact traffic within a 10 km radius. Meanwhile, a shopping mall can impact an area of over 50 km in radius. Thus, it is expected that most trips generated or attracted by the development would be captured within these influence areas. These trips generated and attracted are represented by standard rates for trip and parking generation. This paper reviews the trip and parking generation rates of various rates used in traffic analysis. An assessment of issues and concerns pertaining to local trip and parking rates are discussed and recommendations for future research directions are made based on information derived for this review.
Keywords: Trip generation; Parking generation